Касб танлашга муносабат тизими шакллантириш - замонавий таълим жараёнининг муваффақияти омили (SCIENCE and SOCIETY, 2022)
This article discusses the implementation of reforms in the field of education in our country, on the basis of these reforms, the issues of career guidance for students, preparing them for the choice of a free profession. The article also discusses such aspects of education in recent years in our country as a practical solution to reforms in the field of vocational training of students.